Pengaruh Literasi Keuangan, Risiko Investasi, Sharia Compliance, dan Norma Subjektif dalam Mendorong Minat Berinvestasi pada Instrumen Saham Securities Crowdfunding Syariah di Jakarta - Verina Araminda Prinari; Yudi Ahmad Faisal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of financial literacy, investment risk, sharia compliance, and subjective norms on individual’s interest in investin in sharia-based securities crowdfunding (SCF) stock instruments in Jakarta. A quantitative approach with descriptive method was employed in this research. Primary data were collected through questionnaires distributed to 240 respondents selected using purposive sampling. The population in this study consisted of individuals who are interested in sharia SCF stocks and reside or work in Jakarta. The data were analyzed using structural equation modeling-partial least squares (SEM-PLS). The results indicate that finansial literacy, investment risk, sharia compliance, and subjective norms have a positive and significant influence on investment interest in sharia-based securities crowdfunding stock in Jakarta.